Churchill on religion. The intuition - Pereira, Américo José Pinheira (2022)
Having had an initial twofold education on religion, first under the paradigm of "simple faith" through the example of his Nanny, Mrs. Everest, on which a bourgeois mode of understanding religion was poured at Harrow and Sandhurst, when facing the mortal perils of frontline soldier life, Churchill evolved to a peculiar personal mode of understanding and living the relation with the divine.